KORELASI KEPUASAN MENGHUNI DAN KARAKTERISTIK TEMPAT TINGGAL: STUDI META ANALISIS - Intan Rahmawati (ATRIUM: Jurnal Arsitektur, 2015)
Title: Correlation of Residential Satisfaction and Housing Characteristics: A Meta-Analysis Development of life today shows remarkable changes in social circumstances including the one of which is design manufacture building or residence. The designers often try to give shape according to changes in the environment, but does not fit with the constraints faced. From this it can be seen how the shelter was made which would also be an impact on the behavior of its inhabitants, based on the map of the research results that inhabit satisfaction is influenced by characteristics of the dwelling, such as lighting, size, number and state of the room. From a variety of research on this, it seems less consistency in the results, so we need another way of studying the meta-analysis. The purpose of this study was to assess the results of research that has been done by researchers in the field of architecture and environmental psychology, that housing characteristics are consistently associated with satisfaction of inhabitants. The meta-analysis resulted in the housing characteristics contribute to inhabitants satisfaction.